2008
DOI: 10.1364/oe.16.022003
|View full text |Cite
|
Sign up to set email alerts
|

Optical resonances on sub-wavelength silver lamellar gratings

Abstract: The optical response of sub-wavelength silver lamellar gratings has been theoretically investigated. Two distinct types of resonance have been predicted for incident radiation with E-field perpendicular to the long axis of the wires. The first resonance has been identified as a cavity mode resonance that is associated with transmission enhancement. The second resonance has been identified as an entirely new horizontal plasmon resonance on the incident (and transmission) surfaces of the wires of the grating. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For cavity modes in a single groove in a perfect conductor, it has been shown that end effects lead to a decrease in frequency as the groove is broadened [20]. However, it has been discussed elsewhere [21] that, for very narrow grooves in a finite conductor, as the groove is broadened there is an increase in frequency of the cavity mode due to the finite conductivity, and that in the optical regime, this effect dominates [22]. It is therefore expected that cavity modes, on the structure presented here, will increase in frequency as the grooves are broadened, and furthermore, that the resonance will broaden and diminish.…”
Section: Resultsmentioning
confidence: 99%
“…For cavity modes in a single groove in a perfect conductor, it has been shown that end effects lead to a decrease in frequency as the groove is broadened [20]. However, it has been discussed elsewhere [21] that, for very narrow grooves in a finite conductor, as the groove is broadened there is an increase in frequency of the cavity mode due to the finite conductivity, and that in the optical regime, this effect dominates [22]. It is therefore expected that cavity modes, on the structure presented here, will increase in frequency as the grooves are broadened, and furthermore, that the resonance will broaden and diminish.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy between two curves is less than 5% in the studied range. In fact, our results may be more accurate than those of [3]- [7] as our algorithm's convergence has been proven theoretically (see for details [19]) while the specific forms of the IE used in [3]- [7] do not amend themselves for such a mathematical proof. Here, we understand the convergence in mathematical sense, as possibility of reducing the error of computations by solving progressively larger matrices (many divergent schemes still yield a few correct digits in solution).…”
Section: A Stand-alone Stripmentioning
confidence: 81%
“…This is caused by the effects of extraordinarily large reflection, transmission, emission, and near-field enhancement that have been found in the scattering of light by periodic scatterers. [9][10][11][12] More broadly, these resonances display a variety of Fano shapes near so-called Rayleigh anomalies of associated infinite grating. 10,13,14 Much controversy still exists around these resonances.…”
Section: Introductionmentioning
confidence: 99%
“…waveguide-mode) resonances or "vertical plasmons" observable on the thick strip metal gratings. 11,[33][34][35][36] In the reminder of this paper, Section II presents concise summary of the formulation and method of treatment. Section III deals with numerical study of resonances in the case of H-polarization.…”
Section: Introductionmentioning
confidence: 99%